Performance Evaluation of Highly Admixed Tanzanian Smallholder Dairy Cattle Using SNP Derived Kinship Matrix - Mujibi, Fidalis D. N.; Rao, James; Agaba, Morris; Nyambo, Devotha; Cheruiyot, Evans K.; Kihara, Absolomon; Zhang, Yi; Mrode, Raphael (Frontiers in Genetics, 2019)
The main purpose of this study was to understand the type of dairy cattle that can be optimally used by smallholder farmers in various production environments such that they will maximize their yields without increasing the level of inputs. Anecdotal evidence and previous research suggests that the optimal level of Taurine inheritance in crossbred animals lies between 50% and 75% when considering total productivity in tropical management groups. We set out to assess insitu the relationship between breed composition and productivity for various smallholder production systems in Tanzania. We surveyed 654 smallholder dairy households over a one-year period and grouped them into production clusters. Based on supplementary feeding, milk productivity and sale as well as household wealth status four clusters were described: low-feed-low-output subsistence, medium-feed-low-output subsistence, maize germ intensive semi-commercial and feed intensive commercial management groups. About 800 crossbred cows were genotyped at approximately 150,000 SNP loci and their breed composition determined. Percentage dairyness (proportion of genes from international dairy breeds) was estimated through admixture analysis with Holstein, Friesian, Norwegian Red, Jersey, Guernsey, Ndama, Gir and Zebu as references. Four breed types were defined as RED-GUE, RED-HOL, RED-Zebu, Zebu-RED based on the breeds that make up the top 76% breed composition. A fixed regression model using the G matrix was used to analyze milk yield records. The fitted model accounted for year-month-test-date, parity, age, breed type and the production clusters as fixed effects in the model in addition to random effects of animal and permanent environment effect. Results suggested that RED-Zebu breed type with dairyness between 75 to 85% is the most appropriate for a majority of smallholder management groups. Additionally, for farmers in the feed intensive management group, animals with a Holstein genetic background with at least 75% dairy composition were the best performing. These results indicate that matching breed type to production management group is central to maximizing productivity in smallholder systems. The findings from this study can serve as a basis to inform the development of the dairy sector in Tanzania and beyond.